MEMBANGUN KEAMANAN REGIONAL DI ASEAN DALAM MENANGGULANGI ANCAMAN TERORISME - SUDIRMAN, ARFIN (JWP (Jurnal Wacana Politik), 2017)
ASEAN (Association of Southeast Asian Nations) as a regional cooperation association has a significant roles on harmonizing the counter terrorism effort in the Southeast Asia region. Based on primary and secondary data by using qualitative method, the purpose of this paper is to examine the harmonization of counter terrorism cooperation between ASEAN members. The research found that ASEAN has a set of counter terrorism policies that had been ratified in different times as a form of regional policies harmonization. However in terms of strategic-operational level, the ASEANâs member states has the authority to tackle terrorism issue on their own with the possibility to establish a cooperation with a non ASEAN member state. In addition, the US also has a significant role in assisting counter terrorism effort for ASEANâs states members.